Peran Job Crafting sebagai Mediasi Learning Goal Orientation dan Work Engagement - Ameliasari, Terry Luana (Jurnal Ilmu Manajemen, 2020)
This study aims to determine the role of job crafting as a mediation between learning goal orientation towards work engagement. This research is a quantitative study using a questionnaire method. The sample in this study was 51 employees of PT. Boma Bisma Indra (Persero) Surabaya. Data analysis used Structural Equation Model with the help of the SmartPLS 3.0 program. The results in this study indicate: (1) there is a significant positive effect of learning goal orientation on work engagement, with the t-statistics value of 3,432; (2) there is a significant positive effect of learning goal orientation on job crafting, with the t-statistics value of 8,234; (3) there is a significant positive effect of job crafting on work engagement with the t-statistic value of 4,931; (4) job crafting mediates the effect of learning goal orientation on work engagement, with the t-statistics value of 3,987 then the hypothesis was accepted.